An objective functional evaluation of the flexor carpi ulnaris set of triple tendon transfer in radial nerve palsy. (February 2017) - Latheef, L.; Bhardwaj, P.; Sankaran, A.; Sabapathy, S. R.
This study reports an objective assessment of postoperative function of 11 triple transfers for high radial palsies, using pronator teres for wrist extension, flexor carpi ulnaris for finger extension and palmaris longus for thumb extension. The mean follow-up was 3.3 years. Assessment was done by recording the active ranges of wrist motion, grip strength, wrist and finger strength and work simulation. The mean strength and range of wrist extension were 42% and 86%, respectively, of the contralateral wrist. Other measured movements were within the functional range and work simulation confirmed good restoration of function. The mean DASH score was 3.45, with no patient reporting any specific functional complaints. This study shows that even though the range of wrist motion and the strength of the wrist and fingers are less than normal, hand function remains good. We conclude that the flexor carpi ulnaris set of tendon transfer works well. Level of evidence: 3